Perbandingan Kadar Kreatinin Pre Dan Post Hemodialisa Pada Pasien Gagal Ginjal Kronis - Sudrajat, Agus; Fetriyana, Chelza (Barongko: Jurnal Ilmu Kesehatan, 2023)
Chronic kidney disease is a progressive chronic disease of the kidney nephrons that can affect the body's fluid and electrolyte balance. In this condition, permanent kidney replacement is needed, namely kidney transplantation and hemodialysis. Hemodialysis is a therapy that is mostly done by patients. This study aims to determine the differences in creatinine pre and post hemodialysis in chronic kidney disease patients at Arcamanik General Hospital, Bandung City. The data obtained by the 34 patients will be recorded and displayed in the form of data tabulations and analyzed by the Normality Test using the Shapiro-Wilk with normally distributed data obtained, where the pre hemodialysis p value is 0.970 (p> 0.05) and the post hemodialysis p value is 0.530 (p>0.05). The pre hemodialysis creatinine level averaged 12.83 mg/dL, while the post hemodialysis creatinine level averaged 5.17 mg/dL. From the results it can be seen that the creatinine level before hemodialysis is higher than the creatinine level after hemodialysis. Based on the research conducted, it can be concluded that there is a significant difference in the comparison of pre and post hemodialysis creatinine in chronic kidney disease patients after the data is processed statistically using the Paired T-Test, with a p value of 0.001 (p <0.05).